Description Of Optimization Of Education About The Rights And Obligations Of New Patients And Family : Pilot Study - Krisna, Dimas Adi; Kusumaningsih, Dewi; Kristanto, Eka Yudha; Nopriyanto, Dwi (Fakultas Kedokteran, 2023)
Introduction: Nursing services are part of health services which play a major role in determining health services. Nursing as a profession and nurses as professional staff and are responsible for providing nursing services according to their competence and authority independently or in collaboration with other health members. These patient rights and obligations can be fulfilled by nurses through the orientation carried out by nurses for new patients. New patient orientation is a contract between the nurse and the patient or family where there is an agreement between the nurse and the patient or family in providing nursing care. Objective: Optimize the implementation of education on the rules, rights and obligations of new patients and families through innovative use of welcome books/booklets. Method: This research uses a descriptive research design with a pilot study approach. The sample for this research was nurses in the children's inpatient room at Hospital The instrument used is the SOP observation sheet for implementing new patient admissions used in the room, using the Welcome Book/Booklet. Results: Observation results of the implementation of new patient admissions in the children's inpatient room at Hospital X after using the welcome book/booklet for 5 nurses in the good category. Conclusion: Implementation of new patient admissions through a pilot study approach with analysis using fishbone diagrams and implementation of actions using the PDCA (Plan, Do, Check and Action) concept during the evaluation showed improvements in implementation.Keywords : New Patient Orientation, Rules of Procedure, Patient Rights and Obligations